School Administration Services Information System At Muhammadiyah DIKDASMEN TEGAL SARI II WEB-BASE - Takhir, Said Hambali; Fakhriza, Muhammad; Alda , Muhamad (Ali Institute or Research and Publication, 2022)
At the time of the current era of technological globalization, the need for the Basic Education Council at the branch level is to be able to manage school business charities for more than 2 schools, with hundreds of teachers and students, so that the implementation of data collection is quite complicated and complex. Data collection that is done manually is considered inefficient considering the large number of teaching staff and schools managed by the head of education and education. One of them is at the Tegal Sari II branch which has 8 schools consisting of Kindergarten, Elementary School, and Junior High School. Online administrative services are considered sufficient to be a solution in the implementation of administration, one of the systems that has been widely developed is a website-based information system. One of the programming languages ​​that can be used in website development is PHP and MySQL. This research uses the R&D (Research and Development) method. Researchers conduct research in advance to collect the required amount of data with interviews, then carry out system development and conduct testing and evaluation of the system created.